1993
DOI: 10.1002/jcc.540140112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of computational methods applied to oxazole, thiazole, and other heterocyclic compounds

Abstract: (A variety of computational methods, including the semiempirical techniques AMI, PM3, and MNDO, and the thermochemical basis sets of Benson and Stine, was used to calculate and compare heats of formation M (A-/i) data for optimized geometries of a variety of aromatic and nonaromatic heterocycles. Detailed analyses, including 6-31G' and MP2/6-31G* ab initio calculations, were performed for the oxazole and thiazole heterocycles. The results indicate a scatter among the methods sensitive to the nature of the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…ref. 36). comparison of the AM^ geometries, potential derived charges and dipole moments with ab initio data for some imidazo [l,2-b] pyridazines revealed a good agreement, particularly for the charge values.]…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…ref. 36). comparison of the AM^ geometries, potential derived charges and dipole moments with ab initio data for some imidazo [l,2-b] pyridazines revealed a good agreement, particularly for the charge values.]…”
Section: Resultsmentioning
confidence: 78%
“…Some imidazo[l,2-blpyridazines listed in Tables 1-5 possessed the structural features outlined above (apparently in the proposed spatial arrangements) but showed only poor affinities for the receptor [e.g. (5), (8), (lo), (32), (33), (36)l. This indicated that all substituents and their effects should be considered, but not in isolation.…”
Section: Resultsmentioning
confidence: 99%
“…A counter-anion may approach the S atom, since the space surroundings the S atom is sterically open. AM1 calculations usually give the poorest results for most five-membered aromatic heterocycles with one nitrogen [14] and thus, the N3 atom of thiamine may have positive charge. The heat of formation was calculated to be 130.8 kcal/mol.…”
Section: Geometry Optimization Of the Model Catalystmentioning
confidence: 99%
“…For instance, the computational analyses of the structures (bond length, bond angle, and partial charge distribution) using semi-empirical methods (extended-Huckel calculation for thiamine derivatives [12] and AM1 calculation for thiamine [13]) have been reported. For thiazole and pyrimidine that are the component of thiamine, the most suitable calculation method has been discussed by the comparison between the results of the semi-empirical methods (MNDO, AM1, PM3) [14] or those of the non-empirical ones (RHF/STO-3G, 3-21G, 3-21G*, and 6-31G* levels) [15]. As a former example, Shaffer and Wierschke reported that the PM3 program has given the best semi-empirical results for 4-methylthiazole in comparison with MNDO, AM1, and the Benson method [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation